DEVELOPMENT OF READING SKILLS IN CHILDREN THROUGH FAIRY TALES - Sultonova O'gilkhan Sobirjonovna (Galaxy International Interdisciplinary Research Journal, 2022)
Folk tales are the primary and most important part of child education. Education of a healthy gene pool and mature personnel starts from this period. These values, fairy tales, folk proverbs, which are considered the primary link of the continuous education system, are very important for the child to grow up in a healthy and well-rounded sense in all aspects and to inculcate the knowledge and values ​​that determine the child's entire future into the hearts of the young generation. is a process that has